(untitled) (Comprehensive Journal of Science, 2025)
The study aims to identify the contribution of actuarial accounting in ensuring the sustainability of social security funds by clarifying its contribution in estimating the value of future financial obligations and in managing future financial risks. The study relied on inductive and deductive methods in collecting data from secondary sources, as well as primary sources, which consisted of distributing 35 questionnaires to the study population, represented by the actuarial accounting department of the social security fund. A comprehensive survey of the population was conducted due to its small size, and the SPSS statistical program was used to analyze the collected data. The study reached a set of results, the most important of which is that there is a statistically significant positive effect of estimating the value of future financial obligations on the sustainability of the Social Security Fund, as well as a strong and statistically significant positive effect of managing future financial risks on the sustainability of the Social Security Fund. Therefore, actuarial accounting has a statistically significant impact on ensuring the sustainability of the social security fund. The study made a number of recommendations, the most important of which is the need to strengthen coordination between legislative and administrative bodies to support the application of actuarial accounting, given its importance in the sustainability of social security funds.